The Role of Temperament in the Etiopathogenesis of Bipolar Spectrum Illness. Issue 1 (January 2016) - Fountoulakis, Konstantinos N.; Gonda, Xenia; Koufaki, Ioanna; Hyphantis, Thomas; Cloninger, C. Robert
Abstract : Abstract: Bipolar disorder constitutes a challenge for clinicians in everyday clinical practice. Our knowledge concerning this clinical entity is incomplete, and contemporary classification systems are unable to reflect the complexity of this disorder. The concept of temperament, which was first described in antiquity, provides a helpful framework for synthesizing our knowledge on how the human body works and what determines human behavior. Although the concept of temperament originally included philosophical and sociocultural approaches, the biomedical model is dominant today. It is possible that specific temperaments might constitute vulnerability factors, determine the clinical picture, or modify the course of illness. Temperaments might even act as a bridge between genes and clinical manifestations, thus giving rise to the concept of the bipolar spectrum, with major implications for mental health research and treatment. More specifically, it has been reported that the hyperthymic and the depressive temperaments are related to the more "classic" bipolar disorder, whereas cyclothymic, anxious, and irritable temperaments are related to more complex manifestations and might predict poor response to treatment, violent or suicidal behavior, and high comorbidity. Incorporating of the concept of temperament and the bipolar spectrum into the standard training of psychiatric residents might well result in an improvement of everyday clinical practice.